A novel bilateral lower extremity mirror therapy intervention for individuals with stroke. Issue 12 (December 2016) - Crosby, Lucas D.; Marrocco, Stephanie; Brown, Janet; Patterson, Kara K.
Abstract: Despite improvements made in stroke rehabilitation, motor impairment and gait deficits persist at discharge. New interventions are needed. Mirror therapy has promise as one element of a rehabilitation program. The primary objectives were to 1) describe a bilateral, lower extremity mirror therapy (LE-MT) device and training protocol and 2) investigate the feasibility of LE-MT. A LE-MT device was constructed to train bilateral LE movements for 30 min, 3 times/week for 4 weeks, as an adjunct to physiotherapy in three individuals post-stroke. Sessions were digitally recorded and reviewed to extract feasibility measures; repetitions, rests and session duration. Pre and post measures of gait and motor impairment were taken. Two participants completed 100% of the sessions and a third completed 83% due to a recurrence of pre-existing back pain. Repetitions increased and session duration was maintained. Number of rests decreased for two participants and increased for one participant. Participants reported fatigue and mild muscle soreness but also that the intervention was tolerable. Positive gait changes included increased velocity and decreased variability. LE motor impairment also improved. A bilateral LE-MT adjunct intervention for stroke is feasible and may have positive effects. A history of low back pain should be a precaution.